2016
DOI: 10.3892/ijo.2016.3465
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 promotes tumor growth of human hepatocellular carcinoma by targeting ARID2

Abstract: Aberrant expression of microRNA-155 (miR-155) has been reported in several human cancers and is associated with prognosis of patients. However, the clinical significance of miR‑155 and its underlying mechanisms involved in hepatocarcinogenesis remain to be determined. In this study, we demonstrated that the expression of miR-155 was elevated in both hepatocellular carcinoma (HCC) tissues and cell lines. Clinical association analysis revealed that high expression of miR-155 was correlated with malignant clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…Our previous study found miR‐155 to be the most notably upregulated and miR‐205 the most notably downregulated microRNAs in melanoma, as compared with benign melanocytic tumours . Those data are in accordance with several studies reporting the role of miR‐155 as an oncogene and that of miR‐205‐5p as an oncosuppressor in various types of cancer . Taken together, these findings prompted us to further investigate the target genes of miR‐155 and miR‐205.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study found miR‐155 to be the most notably upregulated and miR‐205 the most notably downregulated microRNAs in melanoma, as compared with benign melanocytic tumours . Those data are in accordance with several studies reporting the role of miR‐155 as an oncogene and that of miR‐205‐5p as an oncosuppressor in various types of cancer . Taken together, these findings prompted us to further investigate the target genes of miR‐155 and miR‐205.…”
Section: Discussionsupporting
confidence: 89%
“…MicroRNA (miR) are small (19–22 nucleotides [nts]) RNA molecules and play crucial functions in the regulation of important processes, such as development, proliferation, differentiation, apoptosis and stress responses . Among these, miR‐155 is a well‐characterized miR and has been proven to participate in inflammatory responses, immune system regulation, hematologic system disorder, cardiovascular diseases and tumorigenesis . MiR‐155 is located on human chromosome 21q21.3 and was first identified as a frequent integration site of the avian leucosis virus .…”
mentioning
confidence: 99%
“…Several groups have reported that ARID2 loss‐of‐function mutations are related to tumor progression and poor survival in patients with HCC and gastric carcinoma . A recent study showed that microRNA‐155 accelerates hepatoma growth through targeting of the ARID2‐mediated Akt phosphorylation pathway . However, little is known about the functional role of ARID2 in HCC, especially in the context of HBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…(36) A recent study showed that microRNA-155 accelerates hepatoma growth through targeting of the ARID2-mediated Akt phosphorylation pathway. (37) However, little is known about the functional role of ARID2 in HCC, especially in the context of HBV replication.…”
Section: Discussionmentioning
confidence: 99%